2023
DOI: 10.1002/glia.24475
|View full text |Cite
|
Sign up to set email alerts
|

Impaired cortical neuronal homeostasis and cognition after diffuse traumatic brain injury are dependent on microglia and type I interferon responses

Jonathan M. Packer,
Chelsea E. Bray,
Nicolas B. Beckman
et al.

Abstract: Neuropsychiatric complications including depression and cognitive decline develop in the years after traumatic brain injury (TBI), negatively affecting quality of life. Microglial and type 1 interferon (IFN‐I) responses are associated with the transition from acute to chronic neuroinflammation after diffuse TBI in mice. Thus, the purpose of this study was to determine if impaired neuronal homeostasis and increased IFN‐I responses intersected after TBI to cause cognitive impairment. Here, the RNA profile of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This drives our strategy to limit TDP-43 overproduction to potentially provide therapeutic approaches to prevent the development of TBI-induced AD neuropathology. Recent research also has increasingly focused on the significant role of microglia in cognitive impairment post-TBI ( Willis et al, 2020 ; Krukowski et al, 2021 ; Bray et al, 2022 ; Packer et al, 2024 ). Common findings across these studies suggest that regulating microglia can reduce cognitive impairment after TBI, hinting at microglia as a potential breakthrough in future treatments for cognitive dysfunction post-TBI.…”
Section: Epidemiology In Chinese Tbi Patients and Potential Etiology ...mentioning
confidence: 99%
“…This drives our strategy to limit TDP-43 overproduction to potentially provide therapeutic approaches to prevent the development of TBI-induced AD neuropathology. Recent research also has increasingly focused on the significant role of microglia in cognitive impairment post-TBI ( Willis et al, 2020 ; Krukowski et al, 2021 ; Bray et al, 2022 ; Packer et al, 2024 ). Common findings across these studies suggest that regulating microglia can reduce cognitive impairment after TBI, hinting at microglia as a potential breakthrough in future treatments for cognitive dysfunction post-TBI.…”
Section: Epidemiology In Chinese Tbi Patients and Potential Etiology ...mentioning
confidence: 99%
“…Microglia depletion reversed suppression of these pathways and prevented the reduction in dendritic complexity at 7 DPI ( Witcher et al, 2021 ). One study investigated the effect of CSF1R inhibition before diffuse TBI using single nuclei sequencing at 7 DPI ( Packer et al, 2023 ). This study identified multiple subclusters, including deep-layer and upper layer cortical neurons.…”
Section: Inhibiting Csf1r On Microglia In Tbimentioning
confidence: 99%
“…TBI induced suppression of cortical neuronal homeostasis (reduction in synaptogenesis and CREB signaling). Microglia depletion before TBI was able to reverse approximately 50% of this gene expression across neuronal subclusters ( Packer et al, 2023 ).…”
Section: Inhibiting Csf1r On Microglia In Tbimentioning
confidence: 99%